2020
DOI: 10.2147/cmar.s234271
|View full text |Cite|
|
Sign up to set email alerts
|

<p>Oral Maintenance Chemotherapy Using S-1/Capecitabine in Metastatic Nasopharyngeal Carcinoma Patients After Systemic Chemotherapy: A Single-Institution Experience</p>

Abstract: Background: In this study, we retrospectively evaluated a series of metastatic nasopharyngeal carcinoma (mNPC) patients who received oral maintenance chemotherapy using S-1/capecitabine after systemic chemotherapy and local radiation therapy, and aimed to explore potential efficient treatment strategies for this subset of patients. Patients and Methods: Thirty-seven patients with mNPC (19 newly diagnosed metastatic patients and 18 metastatic cases after definitive chemoradiotherapy) who received the treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 58 publications
4
7
0
Order By: Relevance
“…22 Another single-arm study also showed superb rates in their reported 3-year OS (87.7%) and PFS (47.6%) for 37 patients with metastatic NPC who received S1/capecitabine maintenance therapy after up-front systemic chemotherapy. 23 Interestingly, two prospective randomized trials from China with similar concepts and designs confirmed the value of additional maintenance chemotherapy as our results in the 2021 ASCO annual meeting. 36,37 Specifically, one study from Gaungxi, China enrolled 183 eligible patients, finding that oral S1 maintenance therapy significantly improved PFS (median: 16.2 vs. 8.7 months, p < 0.001) and OS (median: 32.1 vs. 18.2 months, p < 0.001), whereas the other study from Guangtong, China analyzed 104 randomized patients, showing that oral capecitabine maintenance therapy resulted to a significantly better PFS (HR: 0.43, 95% CI: 0.25-0.73, p = 0.001).…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…22 Another single-arm study also showed superb rates in their reported 3-year OS (87.7%) and PFS (47.6%) for 37 patients with metastatic NPC who received S1/capecitabine maintenance therapy after up-front systemic chemotherapy. 23 Interestingly, two prospective randomized trials from China with similar concepts and designs confirmed the value of additional maintenance chemotherapy as our results in the 2021 ASCO annual meeting. 36,37 Specifically, one study from Gaungxi, China enrolled 183 eligible patients, finding that oral S1 maintenance therapy significantly improved PFS (median: 16.2 vs. 8.7 months, p < 0.001) and OS (median: 32.1 vs. 18.2 months, p < 0.001), whereas the other study from Guangtong, China analyzed 104 randomized patients, showing that oral capecitabine maintenance therapy resulted to a significantly better PFS (HR: 0.43, 95% CI: 0.25-0.73, p = 0.001).…”
Section: Discussionsupporting
confidence: 77%
“…To date and to the best of our knowledge, our literature review found only one similar retrospective study by Sun et al 22 In that study, they explored the role of capecitabine as maintenance therapy in patients with de novo metastatic NPC, revealing a superior OS benefit as compared to the nonmaintenance therapy matching cohort in patients with low pretreatment plasma EBV DNA levels 22 . Another single‐arm study also showed superb rates in their reported 3‐year OS (87.7%) and PFS (47.6%) for 37 patients with metastatic NPC who received S1/capecitabine maintenance therapy after up‐front systemic chemotherapy 23 . Interestingly, two prospective randomized trials from China with similar concepts and designs confirmed the value of additional maintenance chemotherapy as our results in the 2021 ASCO annual meeting 36,37 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Owing to its short halflife and few adverse reactions, S-1 is easy to administer and reduces the pain of intravenous fluids, thereby making patients more receptive, more tolerant, and less likely to develop drug resistance [14][15][16][17][18]. S-1 combined with chemotherapy or radiotherapy for head and neck tumors could have a good effect [19][20][21]. Moreover, when used during radiotherapy, S-1 has been associated with a low recurrence rate, satisfactory long treatment effects, and improved survival quality [9,20].…”
Section: Introductionmentioning
confidence: 99%
“…S-1 combined with chemotherapy or radiotherapy for head and neck tumors could have a good effect [19][20][21]. Moreover, when used during radiotherapy, S-1 has been associated with a low recurrence rate, satisfactory long treatment effects, and improved survival quality [9,20]. In contrast, its efficacy with chemotherapy is not satisfactory [22] and remains controversial.…”
Section: Introductionmentioning
confidence: 99%